ECOLOGICAL APPROACH TO INTIMATE PARTNER VIOLENCE ON INDIGENOUS MEXICAN WOMEN - Gloria Margarita Gurrola Peña; Patricia Balcázar Nava; Alejandra Moysén Chimal; Julieta Garay López; Esteba Esquivel Santoveña (European Scientific Journal, ESJ, 2014)
Intimate Partner violence in indigenous populations has been little explored in Mexico, so the aim of this study was to explore the characteristics of violence that otomi women undergo in the State of Mexico. 50 women living in circumstances of intimate partner violence participated in the study and voluntarily agreed to take deep interviews. The ecological data analysis indicates the testimony of family violence during childhood, overcrowding, poverty and stereotypical and rigid gender roles as the main enhancers of violence against women in this community. The value of the ecological model was shown to recognize the social, familiar and individual characteristics that shape the generation and maintenance of partner violence in indigenous populations.